MADE FOR: um estudo sobre o impacto da internacionalização na imagem de marca na moda de luxo mineira - Carmen Lucia Resende Almeida (2010)
Consumption, which is an essential condition for the individuals, is a contemporary life aspect and it is a great field to be explored by the researchers. However, it is a very poorly investigated area. Fashion also does not receive proper attention, although it has a social, cultural and economic relevance (McCRACKEN, 2003). Thus, this research aimed to promote a dialogue between fashion and consumption, focusing the luxury possessions, and it is clearly related to consumption andtrademark. Even though some foreign literature studies that focus on the luxury consumption can be found (DUBOIS e DUQUESNE, 1993; KAPFERER, 1998; ALLÉRES, 1999, 2000; KAPFERER e BASTIEN, 2009), the theme in Brazil can still be considered under construction. Therefore, there is the need of a careful look at the luxury consumption complex society that lives in abundance and that enjoys spending, acquiring, possessing and consuming. Connected to this context, there isthe cult of trademarks and the perception the consumers and other people have of the values which are transmitted by the trademark, which is called mark image. The Brazilian fashion sector has expanded its business through the internationalization of its goods and trademarks. From such context, the main purpose of this dissertation is to verify and show the effect of the trademark image internationalization on the luxuryfashion realm in Belo Horizonte under the consumers perspective. The theoretical basis used herein was structured from a wide review of the themes Consumption, Fashion (Luxury fashion) and Trademark (Trademark image). Regarding the methodological aspects, this study lies on a qualitative strategy of research, by using the multi-case study method. The content analysis was used as the analysis technique. For treating the data, the software N-Vivo®QSR, version 7.0, was used.The locus of the research corresponds to four fashion sector companies (trademarks) of Minas Gerais: Coven, Mabel Magalhães, Ronaldo Fraga and Victor Dzenk. The corpus of the study was constituted of the managers of the aforesaid trademarks and of three consumers of each trademark, totalizing four managers and twelve consumers. The analysis of the results enabled the study to evidence that the luxury fashion consumption must not be understood only as the consumption of use values, in an utilitarian sense, or of commercial value, but as an active and collective behavior, as an integration to or separation from a group, as the externalization of emotions and wishes, and, thus, fundamentally, as the consumption of meanings. In short, the study showed the existence of a certain relevance that the trademark acquires in the consumption of such luxury goods and it identified the main values(functional, cultural, symbolic and experiential and/or social ones) which lead the studied consumers to choose certain trademark. At last, the relation between the internationalization and all these values in the luxury fashion field was shown, consequently causing an impact on the trademark image.